Characterization of Power Transformer Frequency Response Signature using Finite Element Analysis - Hashemnia, Naser (Curtin University, 2014)
Power transformers are a vital link in electrical transmission and distribution networks. Monitoring and diagnostic techniques are essential to decrease maintenance and improve the reliability of the equipment.This research has developed a novel, versatile, reliable and robust technique for modelling high frequency power transformers. The purpose of this modelling is to enable engineers to conduct sensitivity analyses of FRA in the course of evaluating mechanical defects of power transformer windings. The importance of this new development is that it can be applied successfully to industry transformers of real geometries.